2018
DOI: 10.1371/journal.pone.0195717
|View full text |Cite
|
Sign up to set email alerts
|

In-field and in-vitro study of the moss Leptodictyum riparium as bioindicator of toxic metal pollution in the aquatic environment: Ultrastructural damage, oxidative stress and HSP70 induction

Abstract: This study evaluates the effects of toxic metal pollution in the highly contaminated Sarno River (South Italy), by using the aquatic moss Leptodictyum riparium in bags at 3 representative sites of the river. Biological effects were assessed by metal bioaccumulation, ultrastructural changes, oxidative stress, as Reactive Oxygen Species (ROS) production and Glutathione S-transferase (GST) activity, as well as Heat Shock Proteins 70 (HSP70s) induction. The results showed that L. riparium is a valuable bioindicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 45 publications
3
24
0
Order By: Relevance
“…The slight cytohistological and ultrastructural damage caused by Cd suggests very efficient metal detoxification processes functioning in this moss, despite that-as a general sign of suffering-photochemical efficiency was negatively affected by both Cd concentrations. Interestingly, the mechanisms based on Cd immobilization at the cell wall level have previously been demonstrated not to play a relevant role [31,34]. By contrast, intracellularly-synthesized stress proteins (such as the heat shock protein 70) might be important in repairing the damage caused by Cd, especially at high concentrations, possibly by allowing the correct refolding of Cd-impaired proteins [31,34].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The slight cytohistological and ultrastructural damage caused by Cd suggests very efficient metal detoxification processes functioning in this moss, despite that-as a general sign of suffering-photochemical efficiency was negatively affected by both Cd concentrations. Interestingly, the mechanisms based on Cd immobilization at the cell wall level have previously been demonstrated not to play a relevant role [31,34]. By contrast, intracellularly-synthesized stress proteins (such as the heat shock protein 70) might be important in repairing the damage caused by Cd, especially at high concentrations, possibly by allowing the correct refolding of Cd-impaired proteins [31,34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that the cosmopolitan moss Leptodictyum riparium (Bryophyta) can accumulate, and seemingly tolerate, very high concentrations of toxic metals, including Cd [30][31][32], with a bioconcentration factor higher than that of other plants, even of some angiosperms [33]. Thanks to its apparent tolerance to metal stress and to its high efficiency for metal removal, L. riparium has therefore been proposed as a useful tool for biomonitoring metal contamination, as well as for carrying out phytoremediation projects in polluted areas [31][32][33]. Interestingly, L. riparium performs little Cd immobilization at the cell wall level, and therefore the metal enters the cytosol rather easily [31,34].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Probably because of this characteristic, aquatic mosses have been shown to accumulate more heavy metals (HM) than vascular plants at contaminated sites. Several studies evidenced the ability of Leptodictyum riparium isolated from polluted freshwater to serve as bioindicator, accumulating several heavy metals such as chromium, lead, and zinc [ 3 , 4 ]. Drepanocladus spp.…”
Section: Introductionmentioning
confidence: 99%